IMPROVING THE UNDERSTANDING OF THE CONCEPT AND STUDENT LEARNING ACTIVITIES USED COOPERATIVE LEARNING MODEL TYPE STAD BASED STRUCTURED LKS - Elisa .; Amin Fauzi (Universitas Negeri Medan, 2013)
The objective in this research to improve understanding of the concepts and learning activity of students in solving physics problems through learning models of Cooperative type STAD based structured worksheet. The subjects were first grade students of SMA Swasta Galih Agung numbered 21 people consisted of 21 girls. Object of research is a process of learning by applying Cooperative type STAD model of learning. The research method was applied action research through two learning cycles, each cycle consisting of the stages of planning, implementation, observation and reflection. The results of the data analysis shown that through the application of Cooperative type STAD based structured worksheet model of learning there is an increasing mastery of physics concepts and learning activity first grade students. Increased mastery of physics concepts is seen from increase the number of students who pass out of 10 students (47,62%) to 18 students (85,7%) with averages of 66,62 and 81,09, the learning outcomes completeness criteria of a minimum of 65. Increasing students' learning activity was view from the first and second cycles includes Visual with an average of 81,90% to 91,42%, Oral with an average of 80% to 87,90%, Listening with an average of 81,27% to 84,15%, Writing with an average of 78,08 to 85,41%, Motor with an average of 72,05% to 80%, Mental with an average of 71,44% to 82,20% and Emotional with an average of 73,03% to 82,24%.